Steeper or Faster? Tactical Dispositions to Minimize Oxygen Cost in Ski Mountaineering - Sunde, Arnstein; Christoffersen, Fredrik; Johansen, Jan-Michael; Støren, Øyvind (Frontiers in Sports and Active Living, 2022)
Purpose Investigate the effect of speed, inclination, and use of heel elevator on the oxygen cost of vertical climbing (Cvert) in ski mountaineering. Methods In this study, 19 participants who were (3 women and 16 men) moderate- to well-trained recreational Norwegian ski mountaineers were involved. All participants were tested for VO2max in running, and in a ski mountaineering test on a treadmill, to assess Cvert. The test protocol consisted of 12 4 min work periods at different inclinations from 13 to 23°, with continuous VO2 measurements. After every second work period, the inclination increased by 2°, and speed was decreased accordingly. The speed reduction was based on the equation Vvert = speed · sin(α), where α represents the angle of inclination. Vvert was thus held constant for each work period (854 m·h−1). All work periods were completed twice, with and without a heel elevator. Half of the subjects started with the smallest inclination, and the other half started with the steepest inclination. Results The results showed that Cvert was unchanged at all inclinations except 13°, where there was a significantly higher Cvert, at the same Vvert. Only at 13°, Cvert was higher with the use of heel elevator. There was also a significant trend indicating lower Cvert with use of heel elevator with steeper inclination. Conclusions There seemed to be nothing to gain by choosing detours if the inclination was 13° or less. The use of heel elevator was more advantageous, the steeper the inclination, but at 13° there was a negative effect of using heel elevator.